Heterogeneity in Risk-Taking During the COVID-19 Pandemic: Evidence From the UK Lockdown - Guenther, Benno; Galizzi, Matteo M.; Sanders, Jet G. (Frontiers in Psychology, 2021)
In two pre-registered online studies during the COVID-19 pandemic and the early 2020 lockdown (one of which with a UK representative sample) we elicit risk-tolerance for 1,254 UK residents using four of the most widely applied risk-taking tasks in behavioural economics and psychology. Specifically, participants completed the incentive-compatible Balloon Analogue Risk Task (BART) and the Binswanger-Eckel-Grossman (BEG) multiple lotteries task, as well as the Domain-Specific Risk-Taking Task (DOSPERT) and the self-reported questions for risk-taking used in the German Socio-economic Panel (SOEP) study. In addition, participants in the UK representative sample answered a range of questions about COVID-19-related risky behaviours selected from the UCL COVID-19 Social Survey and the ICL-YouGov survey on COVID-19 behaviours. Consistently with pre-COVID-19 times, we find that risk tolerance during the UK lockdown i) was higher in men than in women and ii) decreased with age. Undocumented in pre-COVID-19 times, we find some evidence for healthier participants displaying significantly higher risk-tolerance for self-reported risk measures. We find no systematic nor robust patterns of association between the COVID-19 risky behaviours and the four risk-taking tasks in our study. Moreover, we find no evidence in support of the so-called “risk compensation” hypothesis. If anything, it appears that participants who took greater risk in real-life COVID-19-relevant risky behaviours (e.g. isolating or taking precautions) also exhibited higher risk-tolerance in our experimental and self-reported risk-taking measures.